Seasonal and Spatial Variations of Meiofauna Communities in Correlation to Environmental Characteristics in the Organic Shrimp Farms of Tam Giang Commune, Nam Can District, Ca Mau Province - Thai, Tran Thanh; Lam, Nguyen Le Que; Quang, Ngo Xuan; Hieu, Ha Hoang (VNU Journal of Science: Natural Sciences and Technology; Vol 34 No 1DO - 10.25073/2588-1140/vnunst.4715, 2018)
Environmental factors and meiofauna communities in the organic shrimp farms located in Tam Giang commune, Nam Can District, Ca Mau province were investigated in March (dry season), July (transfer season) and November (wet season) of 2015. The results recorded that the environmental factors were not quite optimal for shrimp farming such as the high percentage of TN and TOC and anaerobic condition in sediment. The results were also indicated that DO, TOC and TN showed significant correlation with characteristics of meiofauna communities. Following results were indicated that the meiofauna communities were expressed as the high abundance and slightly biodiversity that is a rich natural food sources for shrimp in the organic shrimp farms ponds. Further more, nematoda dominate numerically in the meiofauna communities. Keywords Biodiversity, Ca Mau, mangroves, meiofauna, organic shrimp farms References [1]. S. Trent, J. Williams, C. Thornton, M. Shanahan, Farming the sea, costing the earth: why we must green the blue revolution (2004). [2]. P. N. Hong, H. T. San, Mangroves of Vietnam 7 (1993) IUCN. [3]. B. T. Nga, Hệ thống rừng-tôm trong phát triển bền vững vùng ven biển đồng bằng sông Cửu Long, Tạp chí Khoa học Trường Đại học Cần Thơ 10 (2008) 6. [4]. Ministry of Agriculture and Rural development, 2016. https://tongcucthuysan.gov.vn/en-us/aquaculture/doc-tin/006222/2016-10-28/ca-mau-set-outs-to-become-viet-nams-largest-shrimp-hub. Truy cập ngày 14/8/2017. [5]. Thai agricutural standard (TAS), Organic marine shrimp farming, Royal Gazette 124 (2007) [6]. T. T. Thai, N. T. My Yen, N. Tho, N. X. Quang, Meiofauna in the mangrove–shrimp farms ponds, ca mau province. Journal of Science and Technology, 55 (2017) 271. [7]. N. Tho, V. N. Ut, R. Merckx, Physico‐chemical characteristics of the improved extensive shrimp farming system in the Mekong Delta of Vietnam, Aquaculture Research 42 (2011) 1600. [8]. R. P. Higgins, H. Thiel, Introduction to the Study of Meiofauna, Smithsonian Institute Press, Washington DC, 1988. [9]. B. C. Coull, Role of meiofauna in estuarine soft‐bottom habitats, Austral Ecology 24 (1999) 327. [10]. N. Majdi, W. Traunspurger, Free-living nematodes in the freshwater food web: a review, Journal of nematology, 47(2015) 28. [11]. C. L. Marte, The Food and Feeding Habit of Penaeus Monodon Fabricius Collected From Makato River, Aklan, Philippines (Decapoda Natantia) 1, Crustaceana 38 (1980) 225. [12]. M. Vincx, Meiofauna in marine and freshwater sediments, In G. S. Hall (Ed.), Methods for the examination of organismal diversity in soils and sediments Wallinfort, UK, 1996 [13]. S. Porrello, P. Tomassetti, L. Manzueto, M. G. Finoia, E. Persia, I. Mercatali, P. Stipa, The influence of marine cages on the sediment chemistry in the Western Mediterranean Sea, Aquaculture, 249 (2005) 145. [14]. P. Munsiri, C. E. Boyd, D. Teichert-Coddington, B. F. Hajek, Texture and chemical composition of soils from shrimp ponds near Choluteca, Honduras, Aquaculture International 4 (1996) 157. [15]. C.E. Boyd, Best management practices for water and soil management in shrimp farming. Workshop (2003) in MazatlaŁn, Mexico. [16]. X. N. Quang, A. Vanreusel, N. V. Thanh, N. Smol, Biodiversity of meiofauna in the intertidal Khe Nhan mudflat, Can Gio mangrove forest, Vietnam with special emphasis on free living nematodes, Ocean Science Journal 42 (2007) 135. [17]. X. N. Quang , A. Vanreusel, N. Smol, N. N. Chau, Meiobenthos assemblages in the mekong estuarine system with special focus on free-living marine nematodes, Ocean Science Journal 45 (2010) 213. [18]. S. Vanhove, M. Vincx, D.V. Gansbeke, W. Gijselinck, D. Schram, The meiobenthos of five mangrove vegetation types in Gazi Bay, Kenya, Hydrobiologia 247 (1992) 99. [19]. B. Kondalarao, Distribution of meiobenthic harpacticoid copepods in Gautami-Godavari estuarine system, Indian Journal of Marine Sciences 13 (1984) 80. [20]. A.M.A. Sultan, K. Krishnamurthy, M.J.P. Jeyaseelan,. Energy flows through the benthic ecosystem of the mangroves with special reference to nematodes. Mahasagar Bull. Nat. Inst. Oceanogr., 16 (1983) 317. [21]. A.H. Dye, Vertical and horizontal distribution of meiofauna in mangrove sediments in Transkei, Southern Africa, Estuarine, Coastal and Shelf Science 16 (1983) 591. [22]. D.M. Alongi, Intertidal zonation and seasonality of meiobenthos in tropical mangrove estuaries, Marine Biology 95 (1987) 447. [23]. N. K. Panikkar, Possibilities of further expansion of fish and prawn cultural practices in India, Current Science 21 (1952) 29. [24]. V. C. Chong, A. Sasekumar, Food and feeding habits of the white prawn Penaeus merguiensis, Marine ecology progress series 5 (1981) 185. [25]. Z. A. Ansari, B. S. Ingole, A. H. Abidi, Organic enrichment and benthic fauna–Some ecological consideration, Indian Journal of Geo-Marine Sciences 43 (2014) 554.